Dietary Protein Intake, Meat Consumption, and Dairy Consumption in the Year Preceding Pregnancy and During Pregnancy and Their Associations With the Risk of Gestational Diabetes Mellitus: A Prospective Cohort Study in Southwest China - Liang, Yi; Gong, Yunhui; Zhang, Xiao; Yang, Dagang; Zhao, Danqing; Quan, Liming; Zhou, Rong; Bao, Wei; Cheng, Guo (Frontiers in Endocrinology, 2018)
Background: Gestational diabetes mellitus (GDM) has become a public health problem in China. Objective: To examine the association of dietary protein intake before and during pregnancy with the risk of GDM. Design: Dietary intake before pregnancy and during the first and second trimesters of pregnancy was assessed using food frequency questionnaires in a prospective cohort of pregnant women. To screen GDM, participants underwent an OGTT test during 24-28 weeks of gestation. Cox proportional hazards were used to estimate RRs and 95% CIs for the associations between tertiles of dietary protein and the source of protein intake in different time windows with GDM status. Results: Higher intake of total protein (RR (95% CI): 1.92 (1.10-3.14), p for trend=0.04) or animal protein (1.67 (1.19-2.93), p for trend=0.03) in mid-pregnancy was associated with higher risk of GDM. Vegetable protein intake before or during pregnancy was not related to GDM risk (p for trend>0.05). Moreover, in the mid-pregnancy, participants with higher meat consumption or dairy consumption had a higher risk of GDM. Conclusion: Our study indicated that higher dietary intakes of total protein and animal protein in mid-pregnancy were associated with an increased risk of GDM among pregnant Chinese women.